Akt Inhibition Is Associated With Favorable Immune Profile Changes Within the Tumor Microenvironment of Hormone Receptor Positive, HER2 Negative Breast Cancer - Marks, Douglas K.; Gartrell, Robyn D.; El Asmar, Margueritta; Boboila, Shuobo; Hart, Thomas; Lu, Yan; Pan, Qingfei; Yu, Jiyang; Hibshoosh, Hanina; Guo, Hua; Andreopoulou, Eleni; Wiechmann, Lisa; et al. (Frontiers in Oncology, 2020)
Background: The PI3K/Akt/mTOR pathway in part impacts tumorigenesis through modulation of host immune activity. To assess the effects of Akt inhibition on the tumor micro-environment (TME), we analyzed tumor tissue from patients with operable hormone receptor positive, HER2 negative breast cancer (BC) treated on a presurgical trial with the Akt inhibitor MK-2206. Methods: Quantitative multiplex immunofluorescence (qmIF) was performed using CD3, CD8, CD4, FOXP3, CD68, and pancytokeratin on biopsy and surgical specimens of MK-2206 and untreated, control patients. nanoString was performed on surgical specimens to assess mRNA expression from MK-2206-treated vs. control patients. Results: Increased CD3+CD8+ density was observed in post vs. pre-treatment tissue in the MK-2206-treated vs. control patients (87% vs. 0.2%, p <0.05). MK-2206 was associated with greater expression of interferon signaling genes (e.g. IFI6, p<0.05) and lower expression of myeloid genes (CD163, p<0.05) on differential expression and gene set enrichment analyses. Lower expression of anti-apoptotic genes (BAX) and greater expression of pro-apoptotic genes (BAD) were associated with MK-2206 (p<0.05). Conclusion: Akt inhibition in operable BC was associated with a favorable immune profile in the TME, including increased CD3+CD8+ density and greater expression of interferon genes. Additional studies are warranted, as this may provide rationale for combining Akt inhibition with immunotherapy.